Discovery of the genus Andreimyrme Lelej, 1995 (Hymenoptera: Mutillidae) in India and description of a new species from the Western Ghats - Terine, Joshua B.; Lelej, Arkady S.; Kumar, Girish P. (Zootaxa, 2021)
The Oriental genus Andreimyrme Lelej, 1995 is newly reported from India. A new species A. paniya sp. nov. is described based on a female specimen from Kerala part of Western Ghats. Diagnostic features of this new species to separate it from similar species A. neaera (Mickel, 1935) and A. sarawakensis Lelej, 1996 are discussed. This new species has the mesosoma and metasoma with reddish-brown cuticle which approximates Eastern mimicry ring in North America. Andreimyrme paniya sp. nov. expresses a rare color pattern. In India such color syndromes occur in two species of the tribe Smicromyrmini and two species of the subfamily Dasylabrinae. These species inhabit the tropical moist broadleaf forest ecoregion of southern India. An updated diagnosis for males and females of Andreimyrme is given.